Reproducción de una identidad comarcal y exaltación de un vino: la Fiesta de la Vendimia de Toro - Maria Pilar Panero García (Archivio Antropologico Mediterraneo)
Every year in October in the city of Toro (Spain) is celebrated the Festival of the grape harvest, which has its climax in the popularly known as "Carriage Parade". This feast of exaltation of wine, medicine and important food in the subsistence economies due to its high caloric intake, but which is now consumed as a fashionable product, is the ideal framework for representing the toresana identity. During the parade the center of the city becomes the scene of a staging of the traditional cultural heritage of wine, although in recent history there have been many changes that make what is perceived as traditional is the romantic evocation of a World disappeared. This performance is endorsed and legitimized by a very high participation and by the consent of the group that organizes it and participates year after year.